Comparing rice germplasm groups for growth, grain yield and weed-suppressive ability under aerobic soil conditions - Zhao, D.L.; Atlin, G.N.; Bastiaans, L.; Spiertz, J. H. J. (Wiley, 2006)
Germplasm and cultivars need to be selected as parents for breeding weed‐competitive aerobic rice in the tropics. Forty rice (Oryza sativa) cultivars belonging to the aus, indica and tropical japonica germplasm groups, or derived from crosses among them, were evaluated in adjacent weed‐free and weedy trials in aerobic soil conditions during the wet seasons of 2001–2003. The objectives of this study were to assess vegetative growth, grain yield under weed‐free (YF) and weedy (YW) conditions, and weed‐suppressive ability (WSA) of different germplasm groups. In the first 4 weeks after sowing, indica cultivars had faster growth in height, tillering and crop biomass than other groups. They also had high YF, YW and strong WSA. Aus cultivars were similar to the indica types in early growth and WSA, but were poor in YF. Tropical japonica groups and the group derived from indica/tropical japonica crosses were generally inferior to aus and indica groups in early growth and WSA. Both of their YF and YW were lower than that of the indica group. Therefore, indica germplasm seemed to be most suitable for breeding high‐yielding and weed‐suppressive aerobic rice for the tropics. The relationship of WSA with various traits within tropical japonica germplasm revealed that fast early growth, rather than plant erectness, is crucial to WSA.